1/C Deformations of ads3 Boundary Conditions and the Dym Hierarchy - Pino-Rozas, M; Lara-Díaz, K; Reyes-Lopez, F (Springer Science and Business Media Deutschland GmbH, 2024)
This work introduces a novel family of boundary conditions for AdS3 General Relativity, constructed through a polynomial expansion in negative integer powers of the Brown-Henneaux central charge. The associated dynamics is governed by the Dym hierarchy of integrable equations. It is shown that the infinite set of Dym conserved charges generates an abelian asymptotic symmetry group. Additionally, these boundary conditions encompass black hole solutions, whose thermodynamic properties are examined. © The Author(s) 2024.